The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.orglett.8b01459
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Polar Crossover Reactions of Dienylboronate Complexes: Synthesis of Functionalized Allylboronic Esters

Abstract: Radical-polar crossover reactions of dienylboronate complexes are applied to the synthesis of functionalized secondary and tertiary allylboronic esters. The transition-metal-free three-component coupling uses readily accessible dienylboronate esters as substrates in combination with various sp3/sp2 carbon nucleophiles and commercial alkyl iodides as radical precursors. In the visible light-initiated radical chain process, two new C–C bonds are formed, and the E-double bond geometry in the product allylboronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Inspired by the radical polar crossover reaction of “simple” vinyl boron ate complexes (see Section 2.1), the Studer group investigated dienyl boron ate complexes as radical acceptors . If the addition of the transient C‐radical selectively occurs at the δ‐position of the boron ate complex A , an allyl radical intermediate B is generated.…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp2 Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the radical polar crossover reaction of “simple” vinyl boron ate complexes (see Section 2.1), the Studer group investigated dienyl boron ate complexes as radical acceptors . If the addition of the transient C‐radical selectively occurs at the δ‐position of the boron ate complex A , an allyl radical intermediate B is generated.…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp2 Carbonsmentioning
confidence: 99%
“…Likely, polar effects play a key role in the selective α‐H‐abstraction of these anionic boron ate complexes by the electrophilic CF 3 radical (see below). Moreover, it is well established that CF 3 I is an excellent terminal oxidant for intermediates of type B , rendering this cheap iodide to be the reagent of choice to realize this interesting sequence . Ir(ppy) 3 was employed as a smart initiator upon irradiation with blue LEDs (Φ=8.8).…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp3 Carbonsmentioning
confidence: 99%
“…Melting points were measured on a Kofler bench Reichert‐Jung Heizbank or a melting point apparatus Stuart SMP10 and are uncorrected. Boron substituted 1,3‐dienes 1a , 1b , 1c , 1d , 1e , 1f , 1g , 1'a ,[3b] 1''a , benzylhydroxycarbamate, 2‐nitrosopyridine, were prepared as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, Studer has shown that 1,2 migration of the cationic intermediate 20 (Scheme ) is stereoretentive at the migrating carbon and this allows conversion of enantiomerically‐enriched organoboronic esters into ketones bearing a configurationally defined sterogenic center at the α‐carbon (Scheme , 21) . The same group has also extended the radical‐polar crossover reaction to the construction of allylboronic esters such as 22 from simple dienylboronic ester starting materials …”
Section: Addition Of Electron‐poor Radicals To Four‐coordinate Alkmentioning
confidence: 99%